2022
DOI: 10.17485/ijst/v15i46.1658
|View full text |Cite
|
Sign up to set email alerts
|

A Fraud Prevention and Secure Cognitive SIM Card Registration Model

Abstract: Background: Most subscriber identification module (SIM) which usually finds their way to mobile phone users are primarily unregistered or pre-registered. Criminals buy these SIM cards, which have fake personal information, activate them and then use them as a channel of attacking vulnerable mobile phone users. Objective: to investigate the existing standards of the registration process, the weakness and how fraudsters leverage the shortcomings of the existing registration to attack unsuspecting subscribers. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Satellites aim to provide high quality connections with high QoS and low latency error free signals. [133][134][135][136] We have reviewed extensively over the domain of integrating ML and DL with satellite communications. Issues that have been raised like limited bandwidth and spectrum have been tackled using ML and DL solution with adaptive beamforming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Satellites aim to provide high quality connections with high QoS and low latency error free signals. [133][134][135][136] We have reviewed extensively over the domain of integrating ML and DL with satellite communications. Issues that have been raised like limited bandwidth and spectrum have been tackled using ML and DL solution with adaptive beamforming.…”
Section: Discussionmentioning
confidence: 99%
“…With the aim of creating a fully connected world and the initiation of 5G communication technologies there has been increased attention toward satellites. Satellites aim to provide high quality connections with high QoS and low latency error free signals 133–136 . We have reviewed extensively over the domain of integrating ML and DL with satellite communications.…”
Section: Discussionmentioning
confidence: 99%
“…Rajeev Tripathi, 2021[21] describes Quick Response code as having capacity to encode digits from 0 to 9 and up to 7,089 characters, alphabetical characters in lower and upper case, special characters in storage spaces of up to 4,286, byte chacters up to 2,593, Kanji characters up to 1,817, and structured append characters. Owusu Nyarko Boateng et al, 2022[22], observed that SIM cards can be either registered or not, when they are being used in mobile phones. It is also observed that even registered SIM cards are sometimes registered using fake personal details which is similar to nonexistent identity card.…”
mentioning
confidence: 99%